“Análisis multitemporal de los cambios de cobertura y uso de la tierra en las parroquias Licán y Yaruquíes, periodo 2000 – 2020”. - Almeida Huilcapi, Stephany Camila (2024)
Changes in land use and cover are altered by many factors, primarily anthropic, which lead to significant damage to those who inhabit a territory. These damages include loss of biodiversity, changes in hydrological cycles, erosion processes, and other problems such as soil degradation, habitat loss, and increased greenhouse gas emissions. These issues become imperative to solve. One of the essential characteristics of remote sensing is that it's a tool that allows analyzing this type of modification in the soil over time, with which decisions can be made regarding the order of the territory and, thus, reduce the deterioration of the ecosystem. This work performs a multitemporal analysis of changes in land cover and land use for the Licán and Yaruquíes parishes between 2000 and 2020. In this regard, we mainly used the Google Earth Engine program to implement the Random Forest algorithm and the change detection method, supported by ArcGIS 10.8 software. Our analysis revealed a significant increase in cropland, particularly in the Licán parish. Yaruquíes, on the other hand, has experienced substantial changes across several classes. The rate of change in both areas, in terms of degradation and improvement, is considered moderate. The Built, Cropland, and Tree Cover classes are given priority, although the largest area in Yaruquíes is covered by the Bare Soil or Sparse Vegetation class. These findings underscore the pressing need for improved land management and the implementation of projects that are informed by data on land use and land cover. The situation is urgent, and action is needed now.